2004
DOI: 10.1007/bf02382813
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric power of mixed electronic-ionic conductors II. Case of titanium dioxide

Abstract: Abstract. The purpose of the present work is the determination of the thermopower components corresponding to different charge carriers (electrons, electron holes and ions) for TiO 2 and the use of these data for evaluation of the effect of symmetry between these two properties. The procedure of the determination of these components was based on the following two approximations: 9 The first approximation is based on a symmetrical model assuming a consistency between thermopower and electrical conductivity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…[25][26][27][28][29] Non-stoichiometry and doping can lead to a high-ZT value because of the enhancement of the Seebeck coefficient and electrical conductivity. However, non-stoichiometric TiO x (1oxo2) materials exhibit low thermal conductivity at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Non-stoichiometry and doping can lead to a high-ZT value because of the enhancement of the Seebeck coefficient and electrical conductivity. However, non-stoichiometric TiO x (1oxo2) materials exhibit low thermal conductivity at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…A significant and independent concentration of ionic defects at p O 2 near 1 atm is consistent with the fact that in the above range of oxygen pressures, a significant ionic conductivity is observed (ion transport number t i 50?4-0?6). 34,[36][37][38][39][40] It was also found that the coefficients of self-diffusion of oxygen and titanium are practically independent from p O 2 . [54][55][56][57][58][59][60][61][62] The results of the studies of Nowotny et al 39 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19,24,31,32,[35][36][37][38][39][40][41][42][43] They have shown that TiO 22d is an electronic semiconductor in the whole range of its existence. An n/p type transition occurs near the oxygen pressure of 1 atm at temperatures below 1270 K. 19,20,23,24,[27][28][29][34][35][36][37][38][39][40][41][42][43] The first wider interpretation of the point defect structure was presented by Kofstad,6 who assumed that oxygen vacancies are the dominating type of defects, and near the limit of oxide existence, there is also a significant concentration of interstitial titanium ions. Based both on his own studies and on the results by other authors, 5,7,8 he determined the standard Gibbs free energy of defect formation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a homologous series of reduced early titanium oxides , the so‐called Magnéli phases, came into the focus of thermoelectric research . Structurally related to Ruddlesden–Popper phases through the ReO 3 parent structure , they attracted attention during the 70s due to the occurrence of charge density waves in the low temperature regime .…”
Section: Oxides With Adaptive Structuresmentioning
confidence: 99%
“…Although modeling of the electronic structure is difficult because of the large unit cell and disorder, the degree of reduction in the homologous series allows the targeted manipulation and optimization of the electronic transport properties. So far, only a limited number of studies on the high temperature thermoelectric properties of Magnéli oxides of titanium and related composites are available This group of chemically inert and physically compounds has a potential as stable compounds and may close the gap between n‐type and p‐type oxide materials. Some of the most important results are illustrated and compiled in Fig.…”
Section: Oxides With Adaptive Structuresmentioning
confidence: 99%